1999
DOI: 10.1021/ol9910565
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Pure trans-3,4-Disubstituted Tetrahydrothiophenes from Diastereoselective Thiocarbonyl Ylide Addition to Chiral α,β-Unsaturated Amides

Abstract: Asymmetric 1,3-dipolar cycloadditions of a sulfur-containing 1,3-dipole and α,β-unsaturated camphorsultam amides as dipolarophiles are described. The cycloaddition products, trans-3,4-disubstituted tetrahydrothiophenes, were obtained in high diastereomeric ratios (up to 90:10) and in high yields. Chromatographic removal of the minor diastereomer followed by cleavage of the chiral auxiliary furnished either the enantiomerically pure corresponding alcohol or carboxylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…14 Thus trans-3,4-disubstituted tetrahydrothiophene derivatives are accessible as pure enantiomers via a simple sequence. 14 We have also demonstrated that an a,b-unsaturated dipolarophile containing a b-benzyloxy group functions well as the reactive partner in this cycloaddition sequence (cf. Scheme 2).…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…14 Thus trans-3,4-disubstituted tetrahydrothiophene derivatives are accessible as pure enantiomers via a simple sequence. 14 We have also demonstrated that an a,b-unsaturated dipolarophile containing a b-benzyloxy group functions well as the reactive partner in this cycloaddition sequence (cf. Scheme 2).…”
Section: Methodsmentioning
confidence: 80%
“…Scheme 2). 14 The resulting 3-tetrahydrothienylcarboxamide contains a trans-4-oxygen substituent. It occurred to us that such tetrahydrothiophenes could be used as building blocks for the construction of enantiopure threo-3-methylalkan-2ols after desulfurisation and debenzylation via a simple synthetic sequence.…”
Section: Methodsmentioning
confidence: 99%
“…The NMR data were consistent with those described in the literature. 22 Methyl (E)-2-heptenoate 2: To a solution of (E)-2-heptenoic acid 1 (32 g, 0.25 mol) in methanol (120 mL) was added SOCl 2 (35.7 g, 0.3 mol) dropwise. The mixture was then heated to reflux for 4 h. Most of the methanol and excess SOCl 2 were removed by rotary evaporation.…”
Section: Chiral Gc-o Analysis and Evaluationmentioning
confidence: 99%
“…Chloromethyl trimethylsilylmethyl sulfide was first devised and used as a parent thiocarbonyl ylide synthon by Sakurai in 1986 [23,24], being utilized to prepare di-and tetrahydrothiophenes via 1,3-dipolar cycloadditions by treatment with CsF in acetonitrile in the presence of appropriate dipolarophiles [25]. Indeed, when various SF 5 -aryl-substituted alkynes were used as substrates, the cycloadditions proceeded smoothly to form the respective dihydrothiophenes, 10a, c and d (Scheme 8).…”
Section: Sf 5 -Thiophene Synthesismentioning
confidence: 99%